Stagione 1998 - 1999. - Bertoni, Mario; Colpitt, Francis; Evangelisti, Silvia; Gardner, Colin; Haggerty, Michael David; Meneghelli, Luigi; Muchnic, Suzanne; Plagens, Peter; Ratcliff, Carter; Selwyn, Marc; Vettese, Angela; Weiermair, Peter (Verona : Studio La Città, 1999)
Barth, Uta ; Knoebel, Imi ; McCracken, John ; Mangold, Julia ; Tommasoli, Sirio ; Caccioni, Luca ; Calzolari, Pierpaolo ; Riverhead (New York) ; Fontana, Lucio ; Kosuth, Joseph ; Merz, Mario ; Morellet, François ; Nannucci, Maurizio ; Sonnier, Keith ; Hashimoto, Jacob
biografie
Overzicht tentoonstelling 1998 - 1999
Italiaans & Engels & Duits
boek